e-ABB Kedah state local government - Abu, Roziya; Zakaria, Zaherawati; Mohd Helmi, Mohd Firdaus; Fadzil, Faizal Haini (Universiti Teknologi MARA, Kedah, 2017)
The Kedah State Executive Council is the executive authority of the Government of Kedah, Malaysia. The Council is composed of the Menteri Besar, appointed by the Sultan Kedah who then led the majority of Kedah State Legislative Assembly. This Council is similar in structure and role to the Cabinet of Malaysia, however it is smaller in size. As federal and state responsibilities differ, there are a number of portfolios that differ between the federal and state governments. Members of the Council are selected by the Menteri Besar, appointed by the Sultan. The Council has no ministry, but instead a number of committees; each committee will take care of certain state affairs, activities and departments. Members of the Council are always the chair of a committee. e-ABB Kedah State Local Government is an androids application of a shortened or contracted form of a word or phrase, used to represent the State of Kedah local governments (also known as local councils) who is in charge of handle and managing community needs like waste collection, public recreation facilities and town planning. Currently, the use of multiple word names favoured by many local government agencies has led to the demand for shorter simpler title search engine. e-ABB Kedah State Local Government is develop to fulfil the conveniences needs.